MOTIVASI KERJA DENGAN KINERJA PENYULUH PADA KEGIATAN PENYULUHAN PERTANIAN DI KOTA KENDARI - Manam Manam; Putu Arimbawa; Yoenita Jayadisastra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The work motivation of agricultural extension workers is a key factor influencing their performance in carrying out agricultural extension activities; as such, it plays a strategic role in enhancing farmers' capacity, self-reliance, and well-being, as well as supporting the success of agricultural development in Kendari City. The objective of this study is to examine the relationship between work motivation and the performance of extension workers in agricultural extension activities in Kendari City. The study population consists of all agricultural extension workers at the five Agricultural Extension Centres (BPP) in Kendari City, totalling 33 extension workers. The research sample was determined using the census method, otherwise known as total sampling. The data collection techniques employed in this study encompassed a range of methods, including in-depth interviews, observational studies, a comprehensive review of the existing literature, and detailed documentation. The study's variables encompassed the work motivation and performance of agricultural extension workers. The research data were analysed using a quantitative descriptive analysis approach and inferential analysis. The results of the study indicate that the work motivation of agricultural extension workers in Kendari City falls into the high category, as evidenced by the fulfilment of physiological needs, safety, love and belonging, esteem, and self-actualization. The performance of agricultural extension workers is commensurate with the highest levels in terms of preparation, implementation, evaluation, and reporting of extension activities. The findings of the Spearman's rank correlation test demonstrate that work motivation exhibits a positive and significant relationship with the performance of agricultural extension workers, with a correlation coefficient of 0.602 and a significance level of 0.000. The enhancement of work motivation through recognition, workplace facilities, job security, and career development has been demonstrated to optimally improve the performance of agricultural extension workers.